Rekonstruksi Kurikulum Mata Kuliah Bahasa Indonesia di Era Disrupsi - Fauziah F (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
The era of technological disruption, characterized by the widespread integration of Artificial Intelligence (AI) and automation, necessitates a reorientation of language competencies in higher education. The Indonesian Language Course (Mata Kuliah Bahasa Indonesia/MKBI), as a compulsory subject in the higher education curriculum, often remains confined to the mechanistic and theoretical teaching of grammar. This article aims to formulate a reconstruction of the MKBI curriculum to make it more responsive to contemporary challenges. The study employs a library research method with a content analysis approach to examine literature on curriculum development and advances in instructional technology. The findings indicate that the reconstruction of the MKBI curriculum should shift its focus from merely developing structural linguistic proficiency toward fostering digital literacy, critical thinking skills, academic digital content creation, and academic ethics in the AI era, including strategies to mitigate digital plagiarism. Furthermore, the integration of a Project-Based Learning (PjBL) model centered on digital outputs, along with the use of blended learning media, is recommended as a new framework for transformative MKBI instruction.